Pendampingan Aplikasi Rapor Digital di Madrasah Ibtidaiyah Miftahul Jinan Wonoayu Sidoarjo - Sufinatin Aisidah; Safi'il Anam (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2020)
This Digital Report Card Application training assistance seeks to provide assistance toteachers in the environment MI Miftahul Jinan, in order to be able to follow governmentdemands and the speed of technology flows to make it easier to access student value data and stored digitally and the speed of technology flow to make it easier to access student valuedata and stored digitally and the speed of technology flow to make it easier to access student value data and stored digitally and neatly both in the institution itself and at the Ministry of Religion, Digital Report Card Application training his is done by the lecture method, varies with discussion and question and answer, demonstrations and assignments, with the aim that the participant understand and able to do digital report cars applications optimally. The results showe that the pre-test average score was 60.6, and the post-test value show that the average is 72,5. It can be concluded that there is an increase of 11.9. an N-Gain was obtained of 0.3 in the moderate/sufficent category. Based on the results of the table above, it shows that the majority of training particants experienced an inrease in their test results.